In vitro evaluation of fracture resistance of endodontically treated teeth - Toneva-Stojmenova Verica; Popovska Lidija; Kokalanov Vasko; Toneva-Nikolova Aleksandra; Apostoloski Pavle (Medicinski fakultet i Klinika za stomatologiju, Niš, 2023)
Introduction: Endodontically treated teeth have a worse biomechanical condition compared to intact vital teeth. The literature shows that with endodontic treatment, tooth tissue is lost and fracture resistance is reduced. This paper presents the findings. Aim of study was to determine difference in fracture resistance between intact teeth and endodontically treated and obturated teeth and which type of fracture is the most common. Materials and Methods: For the purpose of this research, 20 extracted single-root intact teeth were used. By random selection, the samples were divided into 2 groups: G1 (negative control group, n = 5) - intact teeth, G2 (experimental group, n = 15) - treated with Hedstrom file + obturated with Gutta-Percha and Endomethasone N. The samples were subjected to compressive pressure on the Universal testing machine, until the moment of breaking. Results: The average pressure value ( ) at which fracture occurred in G1 was 849 N, and in G2 it was 772.33 N. The standard deviation (s) of the pressure value at which the fracture in G1 occurred was 246.86 N, and for G2 it is 810.74 N. The largest percentage of samples had multiple fracture lines (in 100% of G1 samples; in 53.3% of G2 samples). Conclusion: In all groups, the most common fractures according to direction were combined, and according to complexity multiple. Although the pressure values at which the fractures occurred in the first group were significantly higher than in the second group, from the statistical analyses (Student's t-test with a value of 0.69, CI 95%, p < 0.05), we conclude that there is no noticeably significant difference in the average value of the pressure at which a fracture occurs in both groups.